CLAY-BASED INSULATION MATERIAL - Miezis, Kaspars; Martinovs, Andris (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The aim to explore how siltuizolācijas clay material. The first chapter is devoted to the review of the literature, which deals with general information on the minerals Latvian. The second chapter is a look at where the clays are used and what exactly clays used in construction and other fields. The third chapter deals with the laws and regulations of thermal insulation materials. The fourth section addresses clay physical and chemical properties. The fifth chapter describes the experimental part where are displayed all the quantities and substances.